The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/iep.12044
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte ultrastructural damage in β‐thalassaemic mice

Abstract: β-thalassaemia is a hereditary anaemia resulting from the absence or reduction in β-globin chain production. Heart complications related to iron overload are the most serious cause of death in these patients. In this report cardiac pathology of β-thalassaemic mice was evaluated by light and electron microscopy. The study was carried out in thalassaemic mice carrying human β-thalassaemia mutation, IVSII-654 (654), transgenic mice carrying human β(E) -globin transgene insertion (E4), thalassaemic mice with human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…[37][38][39] Also, these mice also had increased heart weight and cardiac iron levels even at the basal condition when compared with normal mice. 37,39 However, the study by Stoyanova et al was the only one not to observe increased cardiac iron accumulation in homozygous (Hbb d3(th) / Hbb d3(th) ) b-thalassemic mice. 38 This discrepancy could be due to the fact that Stoyanova et al used only Prussian blue staining to determine cardiac iron accumulation, which is a less sensitive method than the atomic absorption and colorimetric methods used by other studies.…”
Section: The Hearts Of B-thalassemic Micementioning
confidence: 99%
See 2 more Smart Citations
“…[37][38][39] Also, these mice also had increased heart weight and cardiac iron levels even at the basal condition when compared with normal mice. 37,39 However, the study by Stoyanova et al was the only one not to observe increased cardiac iron accumulation in homozygous (Hbb d3(th) / Hbb d3(th) ) b-thalassemic mice. 38 This discrepancy could be due to the fact that Stoyanova et al used only Prussian blue staining to determine cardiac iron accumulation, which is a less sensitive method than the atomic absorption and colorimetric methods used by other studies.…”
Section: The Hearts Of B-thalassemic Micementioning
confidence: 99%
“…37 Both in vitro and in vivo studies indicated that heterozygous (Hbb th-3 /Hbb þ ) b-thalassemic mice were anemic, had increased heart weight and cardiac iron accumulation when getting old, and had measurable cardiac dysfunction. [13][14][15][16][17][18][19]30,32,33,[37][38][39][40] Moreover, the homozygous (Hbb th1 / Hbb th1 ), (Hbb d3(th) /Hbb d3(th) ) and heterozygous b-thalassemic mice showed a greater severity of anemia and had higher levels of cardiac iron accumulation than the heterozygous (Hbb th-3 /Hbb þ ) b-thalassemic mice did, even though the mice were still young. [37][38][39] A summary of reports regarding cardiac iron accumulation, cardiac function, and mitochondrial function in b-thalassemic mice (in vivo models) is shown in Table 2.…”
Section: The Hearts Of B-thalassemic Micementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to mouse models of β thalassemia, which is the secondary iron overload condition more closely linked to cardiac iron overload [ 63 ], animal models involving ablation of genes that are inactivated in hereditary hemochromatosis also represent useful and validated models of body (and heart) iron overload. Mouse models involving HFE [ 64 ], hemojuvelin [ 32 , 65 ], hepcidin [ 66 ], and transferrin receptor 2 (TfR2) [ 64 ] inactivation lead to iron loading phenotypes ranging from mild to severe.…”
Section: Preclinical Animal Models Of Cardiac Iron Overloadmentioning
confidence: 99%
“…Tail DNA was used to verify the genotype of each mouse. The phenotype of hemizygous ␤ IVSII-654 mice was categorized as ␤-thalassemic intermedia with iron deposition in the heart and liver, and imbalanced globin synthesis with ␣-to-␤-globin ratio of 1.26 (19,24,26). The homozygous ␤ IVSII-654 genotype is lethal, and the fetus usually dies in utero.…”
Section: Animalsmentioning
confidence: 99%